Pembuatan Biodiesel dari Limbah Ikan Baung Dengan Katalis Padat Lempung - Sukiman Hernanda; Syaiful Bahri; Yusnimar Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Biodiesel as an alternative diesel fuel are made from renewable biological resources, such as vegetable oils and animal fats. In Indonesia, fish production increase every year, so the waste of fish disposal usually is rising as well. Therefore, it is necessary to take advantage of new innovations of fish waste to biodiesel. In this research, conversion of the fish baung disposal to biodiesel has been done. By using a clay catalyst “lempung cengar”. Firstly, the fish disposal was heated for 4 hours. Then, oil was extracted from the fish disposal by pressed manually. Afterward, oil was converse to biodiesel by using a transesterification reaction with methanol as a reactan and a lempung cengar catalyst. The transesterification reaction was conducted under condition temperature 600C, stirring ± 150 rpm and a reaction time 210 minutes. In order to get a biodiesel yield maximally, variations of ratios sample and methanol (1:3; 1:6; 1:9), variation of a clay catalyst (0.5%, 1%, 1.5% w/w) were applied in this research. The result showed than biodiesel yield maximum around 78.01%, under condition ratio between oil and methanol 1:9 and catalyst 1% of amount oil total. Based on physical properties analysist of biodiesel it has density 882 kg/m3, viscosity 5.18 cSt, acid number 0.63 mg-KOH/gr sample, and heating value 1450C respectively. In addition, oil was determined it is chemical properties by GC-MS method before it was applied in the transesterification reaction. Oil has oleat acid 49.10%, behenat acid 29.34%, stearat acid 4.69%, 9 heksadekanoat acid 2.64%, and palmitat acid 0.22%. Key word: Fish oil, Baung fish, Biodiesel, Clay catalyst, Transesterification reaction